1979
DOI: 10.1104/pp.63.3.511
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Partial Characterization of Transfer RNAs from Astragalus bisulcatus

Abstract: A procedure has been developed for the isolation of transfer RNA from the selenium accumulator plant Astragalus bisukatus. This material appears free of interfering phenolic compounds, has a high guanosine to cytidine ratio, shows a major and modified nucleoside composition characteristic of plant transfer RNAs, and exhibits chromatographic and electrophoretic properties similar to transfer RNAs from other weUl studied bacterial and plant systems. RNAs isolated from A. bisukatus seedlings incubated in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1980
1980
1993
1993

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Is 4-Selenouridine a tRNA Component? Although earlier reports indicated that 4-selenouridine is a constituent of E. coli tRNAs (Hoffman & McConnell, 1974;Prasado Rao & Cherayil, 1974;Young & Kaiser, 1979), the ion-exchange and thin-layer chromatographic procedures available at the time lacked the resolving power necessary to distinguish between selenonucleosides and the numerous degradation products generated by the prolonged alkaline digestion procedures that were employed. In the present studies using rapid enzymic digestion procedures and the much more powerful analytical methods now available, we have not detected 4-selenouridine in the tRNA populations of E. coli, C. sticklandii, or M. vannielii.…”
Section: Resultsmentioning
confidence: 99%
“…Is 4-Selenouridine a tRNA Component? Although earlier reports indicated that 4-selenouridine is a constituent of E. coli tRNAs (Hoffman & McConnell, 1974;Prasado Rao & Cherayil, 1974;Young & Kaiser, 1979), the ion-exchange and thin-layer chromatographic procedures available at the time lacked the resolving power necessary to distinguish between selenonucleosides and the numerous degradation products generated by the prolonged alkaline digestion procedures that were employed. In the present studies using rapid enzymic digestion procedures and the much more powerful analytical methods now available, we have not detected 4-selenouridine in the tRNA populations of E. coli, C. sticklandii, or M. vannielii.…”
Section: Resultsmentioning
confidence: 99%
“…Transfer-RNAs (tRNAs) that contain Se appear to be ubiquitous among all groups of organisms (Mayland et aI., 1989). In plants, Young and Kaiser (1979) detected tRNA, which incorporated some Se, in the Seaccumulator Astragalus bisulcatus. In a variety of higher plants and Chlamydomonas, Wen et al, (1988) demonstrated 75Se-tRNA upon supplying the plants with [ 75S eJ selenite.…”
Section: Biosynthesis Ofselenoproteinsmentioning
confidence: 99%
“…When selenium was detected earlier in the tRNAs ofEscherichia coli (3,4) in the form of selenium-modified bases, it was thought to have resulted from the nonspecific substitution of the element for sulfur, but recent studies show that selenium in these tRNAs is a normal component (5) and is incorporated by means ofa highly specific process (6). The tRNAs of two strictly anaerobic bacteria, Clostrtidium sticklandii and Methanococcus vannielii, have a higher content of selenium and this is distributed among four to six seleno-tRNA species (7,8).…”
mentioning
confidence: 99%